From wild to mild and back again: envisioning a new model of crop improvement strategies - Pratt, Richard C.; Kantar, Michael Benjamin; Fumia, Nathan; Nankar, Amol N. (Frontiers in Horticulture, 2024)
Climate change is creating a leverage point in plant breeding. We must rethink the way we employ plant breeding, utilize genetic diversity, and prioritize edible plant production across the landscape. A long-term strategy to 'redirect' the process of crop domestication that prioritizes the generation of abiotic and biotic stress tolerant cultivars is needed. A proposed neo-domestication strategy is presented as a case study. It entails the re-domestication of chile by retro-crossing of modern plant cultivars with landraces and a desert-adapted wild relative. An organized, collaborative effort could reintroduce stress tolerance genes that will render new cultivars more tolerant to challenges imposed by climate change. Purposeful populations generated using a broad spectrum of genetic diversity could also provide the basis for an evolutionary-participatory plant breeding process. The process must recognize the need for a paradigm-shift in our resource allocation and breeding strategies. To succeed, a shared vision for neo-domestication of chile must recognize the importance of human cultural values and the need for sustained cooperation among stakeholders.